Jejunal Dieulafoy's Lesion: A Systematic Review of Evaluation, Diagnosis, and Management - Adnan Malik MD; Faisal Inayat MBBS; Muhammad Hassan Naeem Goraya MBBS; Talal Almas BS; Rizwan Ishtiaq MD; Sohira Malik MBBS; Zahid Ijaz Tarar MD (SAGE Publishing, 2021)
Jejunal Dieulafoy's lesion is an exceedingly rare but important cause of gastrointestinal bleeding. It frequently presents as a diagnostic and therapeutic conundrum due to the rare occurrence, intermittent bleeding symptoms often requiring prompt clinical action, variability in the detection and treatment methods, and the risk of rebleeding. We performed a systematic literature search of MEDLINE, Cochrane, Embase, and Scopus databases regarding jejunal Dieulafoy's lesio from inception till June 2020. A total of 136 cases were retrieved from 76 articles. The mean age was 55 ± 24 years, with 55% of cases reported in males. Patients commonly presented with melena (33%), obscure-overt gastrointestinal bleeding (29%), and hemodynamic compromise (20%). Hypertension (26%), prior gastrointestinal surgery (14%), and valvular heart disease (13%) were the major underlying disorders. Conventional endoscopy often failed but single- and double-balloon enteroscopy identified the lesion in 96% and 98% of patients, respectively. There was no consensus on the treatment. Endoscopic therapy was instituted in 64% of patients. Combination therapy (34%) with two or more endoscopic modalities, was the preferred approach. With regard to endoscopic monotherapy, hemoclipping (19%) and argon plasma coagulation (4%) were frequently employed procedures. Furthermore, direct surgical intervention in 32% and angiographic embolization was performed in 4% of patients. The rebleeding rate was 13.4%, with a mean follow-up duration of 17.6 ± 21.98 months. The overall mortality rate was 4.4%. Jejunal Dieulafoy's lesion is still difficult to diagnose and manage. Although the standard diagnostic and therapeutic modalities remain to be determined, device-assisted enteroscopy might yield promising outcomes.